The cold response regulator CBF1 promotes Arabidopsis hypocotyl growth at ambient temperatures. (25th May 2020) - Dong, Xiaojing; Yan, Yan; Jiang, Bochen; Shi, Yiting; Jia, Yuxin; Cheng, Jinkui; Shi, Yihao; Kang, Juqing; Li, Hong; Zhang, Dun; Qi, Lijuan; Han, Run; et al.
Abstract: Light and temperature are two core environmental factors that coordinately regulate plant growth and survival throughout their entire life cycle. However, the mechanisms integrating light and temperature signaling pathways in plants remain poorly understood. Here, we report that CBF1, an AP2/ERF‐family transcription factor essential for plant cold acclimation, promotes hypocotyl growth under ambient temperatures in Arabidopsis . We show that CBF1 increases the protein abundance of PIF4 and PIF5, two phytochrome‐interacting bHLH‐family transcription factors that play pivotal roles in modulating plant growth and development, by directly binding to their promoters to induce their gene expression, and by inhibiting their interaction with phyB in the light. Moreover, our data demonstrate that CBF1 promotes PIF4/PIF5 protein accumulation and hypocotyl growth at both 22°C and 17°C, but not at 4°C, with a more prominent role at 17°C than at 22°C. Together, our study reveals that CBF1 integrates light and temperature control of hypocotyl growth by promoting PIF4 and PIF5 protein abundance in the light, thus providing insights into the integration mechanisms of light and temperature signaling pathways in plants. Synopsis: CBF1, a key regulator of plant cold acclimation, enhances Arabidopsis hypocotyl growth under ambient temperatures by promoting light‐dependent accumulation of phytochrome‐interacting transcription factors PIF4 and PIF5. CBF1 thus integrates light and temperature control of hypocotyl growth in Arabidopsis . CBF1 physically interacts with phytochromes phyA and phyB. phyA and phyB increase CBF1 protein levels in the light. CBF1 increases PIF4/PIF5 protein levels through transcriptional and post‐translational regulatory mechanisms. CBF1 regulation of PIF4/PIF5 protein abundance and hypocotyl growth is temperature‐dependent. Abstract : Cold‐inducible transcription factor CBF1 integrates light and temperature control of seedling growth by inducing accumulation of light response proteins PIF4/PIF5.